Discovery of Potential Biomarkers for Postmenopausal Osteoporosis Based on Untargeted GC/LC-MS - Kou, Jun; He, Chunyang; Cui, Lin; Zhang, Zhengping; Wang, Wei; Tan, Li; Liu, Da; Zheng, Wei; Gu, Wei; Xia, Ning (Frontiers in Endocrinology, 2022)
Purpose: As an important public health problem, osteoporosis (OP) patients in China are also in an upward trend year by year. As a standard method for diagnosing OP, Dual energy X-ray absorptiometry (DXA) can not analyze the pathological process, but only see the results. It is difficult to evaluate the the early diagnosis of OP. Our study was carried out through a serum metabolomic study of OP in Chinese postmenopausal female on untargeted Gaschromatography (GC)/Liquid chromatography (LC)-mass spectrometry (MS) to find possible diagnostic markers. Materials and Methods: 50 Chinese postmenopausal female with osteoporosis and 50 age-matched female were selected as normal controls. We first used untargeted GC/LC-MS to analyze the serum of these participants, and then combined with a large number of multivariate statistical analysis to analyze the data. Finally, based on multidimensional analysis of the metabolites, the most critical metabolites were considered to be biomarkers of OP in postmenopausal females. Further, biomarkers identified relevant metabolic pathways, followed by a map of metabolic pathways found in the database. Results: We found that there may be metabolic pathway disorders like glucose metabolism, lipid metabolism and amino acid metabolism in postmenopausal female with OP. 18 differential metabolites are considered to the potential biomarkers of OP in postmenopausal female which are a major factor in metabolism and bone physiological function Conclusion: These findings can be applied to clinical work through further validation studies. It also shows that metabonomic analysis has great potential in the application of early diagnosis and recurrence monitoring in postmenopausal OP female.